The Effect of Annealing Temperature and Quenching Media Variations On Heat Treatment Process of Cu-Zn-Al Shape Memory Alloys For Shape Memory Effect and Microstructure - Mavindra Ramadhani; Rochman Rochiem; Rizki Rizki; M Arfani (Institut Teknologi Adhi Tama Surabaya, 2023)
Shape Memory Alloys (SMA) is a material that can return to its original shape after undergoing mechanical deformation. The most commonly SMA material used is the Ni-Ti alloy. However, it is high cost. So that it is necessary to have alternative materials, for instance Cu-Zn-Al. Several studies related to Cu-Zn-Al Shape Memory Alloys have poor mechanical properties. So there further research required in order to determine the heat treatment process of Cu-Zn-Al Shape Memory Alloys. In this study Cu-21Zn-5Al alloys were given heat treatment with annealing temperature variations (425;550;600°C) and cooling media (brine, dry ice). Annealing process affects the mechanical properties and microstructure of the test material. Cooling media results the cooling rate during solution treatment. Tests in this study include hardness test, metallographic test, XRD test, DSC test, and SME test. From the test results, it was found that all the test variables have the Shape Memory Effect. The variable that had the greatest recovery (38.3%) was annealing temperature of 450°C with the cooling solution media using brine. In addition, the most rapid cooling occurs in the brine cooling media.